Novels for students. presenting analysis, context, and criticism on commonly studied novels / Volume 24 - 4 0 16; Milne, Ira Mark.; 5 (Detroit : Thomson/Gale, 2007)
Contains profiles of twelve commonly read novels, each including an introduction to the story and its author, a plot summary, descriptions of characters, analysis of themes and style, discussion of historical context, a critical overview, and other related information.
Includes bibliographical references and indexes.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism.;History and criticism. -- American literature;English literature;German literature;New Zealand literature;Swiss literature;American literature;English literature;German literature;New Zealand literature;Swiss literature; 20; 2